ANALISIS PENGELOLAAN ASET TETAP SEKOLAH NEGERI DI LINGKUNGAN PEMERINTAH KABUPATEN MINAHASA UTARA - Kaligis, Elivira Amelia; Kalangi, Lintje; Gamaliel, Hendrik (JURNAL RISET AKUNTANSI DAN AUDITING "GOODWILL", 2021)
This study aims to analyze the suitability of the implementation of regional asset management with the regulations set by the Government, analyze the constraints faced in the management of local assets and efforts to improve the management of fixed assets of public schools in the North Minahasa Regency environment for the better. This is a qualitative study with exploratory approach. Data were obtained through in depth interview technique, partisipative observation dan documentation study. The result of this research the management of public school fixed assets within the North Minahasa Regency Government is guided by Permendagri No. 19 of 2016 which includes activities for planning needs and budgeting, procurement, use, utilization, security and maintenance, assessment, transfer, destruction, write-off, administration and coaching, supervision and control. There are no fixed assets of state schools that are used for asset utilization activities. There are still problems in every implementation of state school fixed asset management activities. The obstacles encountered in the management of school fixed assets are the absence of a commitment to stipulate Regional Regulations related to the management of regional property, human resources are not sufficient, coordination and communication is still weak, budget resources and facilities are not sufficient, and SIMDA BMD application has not been integrated with SIMDA Keuangan. Efforts are being made to increase the commitment of all related parties, human resource capacity building, improved coordination and communication, asset security, as well as control and supervision. However, this effort still needs to be supported by the establishment of regulations including the Operating System and Procedures, education and training for human resources, collection of proof of land ownership in the context of certification, reward and punishment system, regular reconciliation, asset inventory, integrated information system and intensify development, supervision and control activities.